2003
DOI: 10.1182/blood-2002-08-2353
|View full text |Cite
|
Sign up to set email alerts
|

Deletion or replacement of the second EGF-like domain of protein S results in loss of APC cofactor activity

Abstract: Human protein S (PS), a cofactor of anticoagulant-activated protein C (APC), is a modular protein containing 4 epidermal growth factor (EGF)-like domains. EGF1 appears to mediate PS interaction with APC, but the roles of EGFs 2, 3, and 4 are less clear. We synthesized PS variants lacking single EGF domains (EGF2, 3, or 4) and assessed their APC cofactor activity in a factor Va inactivation assay. The variant lacking EGF2 (variant 134) showed the most dramatic loss of activity (ϳ10% of recombinant wild-type PS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 25 publications
2
44
1
Order By: Relevance
“…In addition, EGFrps composed of only standard EGF-like domains showed only minimal PS binding activity, which is consistent with the previous observation that, although protein S contained four tandem repeats of the EGFlike domain, its N-terminal Gla domain is responsible for binding to the appropriate phospholipid membranes in the presence of Ca 2ϩ ions (27). However, a recent study showed that EGF-like domains are also important for protein S activity and suggested that EGF modules may be able to constrain the protein S molecule in an appropriate configuration (21). This is consistent with our observation that at least four tandem repeats of the EGF-like domain were required for binding to PS, which suggests that at least four repeats of the EGF-like domains may be necessary to form a conformation that presents the second atypical EGF-like domain in the proper orientation to target PS.…”
Section: Discussionsupporting
confidence: 79%
“…In addition, EGFrps composed of only standard EGF-like domains showed only minimal PS binding activity, which is consistent with the previous observation that, although protein S contained four tandem repeats of the EGFlike domain, its N-terminal Gla domain is responsible for binding to the appropriate phospholipid membranes in the presence of Ca 2ϩ ions (27). However, a recent study showed that EGF-like domains are also important for protein S activity and suggested that EGF modules may be able to constrain the protein S molecule in an appropriate configuration (21). This is consistent with our observation that at least four tandem repeats of the EGF-like domain were required for binding to PS, which suggests that at least four repeats of the EGF-like domains may be necessary to form a conformation that presents the second atypical EGF-like domain in the proper orientation to target PS.…”
Section: Discussionsupporting
confidence: 79%
“…A recent report has suggested a role for EGF2, since APC cofactor function was lost upon its replacement or deletion. 45 This suggestion is supported by the association of qualitative PS deficiency with naturally occurring mutations in EGF2 (Lys155Glu 46 and Cys134Phe 47 ). EGF4 of PS has also been suggested to be important to keep EGF1 in optimal alignment for interaction with APC, 39 although a recombinant EGF4 alone has failed to exhibit APC cofactor activity in a clotting assay.…”
Section: Apc-dependent Anticoagulant Functions Of Psmentioning
confidence: 94%
“…Despite numerous studies describing the important protein S domains/residues for protein S cofactor function with APC (22,26,28,37), the mapping of APC residues involved in mediating the interaction with protein S has been limited. One study, however, broadly implicated residues 22-45 of the APC Gla domain in enabling protein S to act as an APC cofactor (18).…”
Section: Discussionmentioning
confidence: 99%